Repercussions of negatively selective migration for the behavior of non-migrants when preferences are social - Oded Stark; Wiktor Budzinski (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
We study how the work effort and output of non-migrants in a village economy are affected when a member of the village population migrates. Given that individuals dislike low relative income, and that migration modifies the social space of the non-migrants, we show why and how the non-migrants adjust their work effort and output in response to the migration-generated change in their social space. When migration is negatively selective such that the least productive individual departs, the output of the non-migrants increases. While as a consequence of this migration statically calculated average productivity rises, we identify a dynamic repercussion that compounds the static one.
urn:nbn:de:bsz:21-dspace-875573
Keywords: D01; D31; J24; O15; 330; Social preferences; Distaste for low relative income; Work effort; Per capita output; Migration